Penilaian Kandungan Zat Organik dalam Air Sumur Desa Kaliserayu Sientis: Studi Mengenai Kepatuhan Standar Kesehatan - Tambunan, Vini Novalia; Kardhinata, E. Harso; Karim, Abdul; Nasution, Jamilah; Riyanto, Riyanto (Universitas Medan Area, 2024)
This study aims to evaluate the compliance of well water quality in Desa Kaliserayu Sientes with the regulations set forth in the Minister of Health of the Republic of Indonesia Regulation No. 416/MENKES/PER/IX/1990 regarding the criteria and supervision of water quality. The method employed is descriptive, involving the measurement of potassium permanganate levels using the permanganometry technique. Data analysis was conducted to assess the organic matter content in well water in Desa Kaliserayu Sientis, Percut Sei Tuan District, Deli Serdang Regency. The research findings indicate variations in organic matter content (expressed in KMnO4), with average values ranging from 10.70 to 46.60 mg/l. These findings suggest that some samples of well water in the area exceed the standard limits permitted by health regulations. The implications of these results underscore the importance of heightened attention to monitoring and managing the quality of well water in Desa Kaliserayu Sientis to safeguard public health and meet established water quality standards.